Type I interferons and SARS-CoV-2: from cells to organisms. (February 2022) - Bastard, Paul; Zhang, Qian; Zhang, Shen-Ying; Jouanguy, Emmanuelle; Casanova, Jean-Laurent
Abstract : Type I interferons (IFNs) have broad and potent antiviral activity. We review the interplay between type I IFNs and SARS-CoV-2. Human cells infected with SARS-CoV-2 in vitro produce low levels of type I IFNs, and SARS-CoV-2 proteins can inhibit various steps in type I IFN production and response. Exogenous type I IFNs inhibit viral growth in vitro . In various animal species infected in vivo, type I IFN deficiencies underlie higher viral loads and more severe disease than in control animals. The early administration of exogenous type I IFNs improves infection control. In humans, inborn errors of, and auto-antibodies against type I IFNs underlie life-threatening COVID-19 pneumonia. Overall, type I IFNs are essential for host defense against SARS-CoV-2 in individual cells and whole organisms.